Pemaknaan Perselingkuhan Ayah dalam Pemilihan Pasangan pada Perempuan Dewasa Awal - Tifanny Angellina; Indriyani Santoso (PT. PENERBIT TIGA MUTIARA, 2026)
The phenomenon of infidelity within families constitutes a significant social issue, as it not only undermines spousal relationships but also leaves enduring psychological wounds on children who witness it, particularly women entering early adulthood when they begin to establish romantic relationships. This study focuses on how early adult women interpret their experiences of witnessing paternal infidelity and the implications of these experiences for trust, commitment, emotional dynamics, and partner selection processes. A qualitative approach with a phenomenological design was employed to explore the subjective experiences of three early adult women aged 20-22 who encountered such events during adolescence. The findings indicate that these experiences are interpreted as traumatic, giving rise to anxiety, fear of betrayal, and difficulties in developing trust, while simultaneously fostering heightened vigilance and selectivity in choosing partners, with an emphasis on loyalty, communication, and emotional security. The emerging psychological dynamics include trust issues, a tendency to avoid conflict, and a strong need for emotional stability, which are addressed through conscious efforts to build healthier relationships characterized by open communication and effective emotional regulation. The study concludes that the subjective meaning-making of paternal infidelity plays a crucial role in shaping relational patterns, perceptions of romantic relationships, and partner selection decisions among early adult women. The novelty of this research lies in its emphasis on the meaning-making dimension, which not only reveals psychological impacts but also highlights resilience and the transformation of traumatic experiences into a foundation for more adaptive and constructive relationships.